Assessing the Economic Impact of Inversion Tillage, Cover Crops, and Herbicide Regimes in Palmer Amaranth (Amaranthus palmeri) Infested Cotton. (29th November 2016) - Duzy, Leah M.; Price, Andrew J.; Balkcom, Kipling S.; Aulakh, Jatinder S.
Abstract : Cotton ( Gossypium hirsutum L.) producers in Alabama are faced with a rapidly expanding problem that decreases yields and increases production costs: herbicide-resistant weeds. Producers increasingly rely on integrated weed management strategies that raise production costs. This analysis evaluated how tillage, cover crops, and herbicide regime affected net returns above variable treatment costs (net returns) for cotton production in Alabama from 2009 to 2011 under pressure from Palmer amaranth ( Amaranthus palmeri S. Wats.). Annual net returns were compared for two tillage treatments (inversion and noninversion tillage), three cover crops (crimson clover [ Trifolium incarnatum L.], cereal rye [ Secale cereal L.], and winter fallow), and three herbicide regimes (PRE, POST, and PRE+POST). Results indicate that under heavy Palmer amaranth population densities one year of inversion tillage followed by two years of noninversion tillage, along with a POST or PRE+POST herbicide application had the highest net returns in the first year; however, the economic benefit of inversion tillage, across all herbicide treatments, was nonexistent in 2010 and 2011. Cotton producers with Palmer amaranth infestations would likely benefit from cultural controls, in conjunction with herbicide applications, as part of their weed management system to increase net returns.